2013
DOI: 10.1111/maec.12072
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and temporal fluctuations of epiphytes and sessile invertebrates on the rhizomesPosidonia oceanicain a seagrass meadow offTunisia

Abstract: The aim of this work is to study the temporal dynamics of rhizome epiphytes and sessile animals living on the rhizomes of the seagrass Posidonia oceanica in the east of Tunisia. on a fringing reef located in Chebba. Rhizomes were sampled by SCUBA diving at three stations. Samples were examined with a microscope to estimate the cover of macroinvertebrate and macroalgal organisms on the top 10 cm of each rhizome. Results revealed a high diversity of epiphytes on P. oceanica rhizomes with a dominance of red and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Both biomass and percentage cover of macro-epiphytic leaves show a seasonal variability with the high values detected in summer. The variability of assemblages and biomass founded in the present study agrees with those described for P. oceanica meadows in the southern coast of Tunisia by Ben Brahim et al [25,36] and by Mabrouk et al [20] in the region of Mahdia eastern coast of Tunisia, where biomass of macro-epiphytes on leaves of P. oceanica was high in summer and low in winter. Similar results were reported by Zakhama-Sraieb et al [37] in Port El Kantaoui, Tunisia where summer appears a sensitive season marked by the high development and dominance by encrusting Corallinaceae and opportunistic macroalgal species which can reach high cover.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Both biomass and percentage cover of macro-epiphytic leaves show a seasonal variability with the high values detected in summer. The variability of assemblages and biomass founded in the present study agrees with those described for P. oceanica meadows in the southern coast of Tunisia by Ben Brahim et al [25,36] and by Mabrouk et al [20] in the region of Mahdia eastern coast of Tunisia, where biomass of macro-epiphytes on leaves of P. oceanica was high in summer and low in winter. Similar results were reported by Zakhama-Sraieb et al [37] in Port El Kantaoui, Tunisia where summer appears a sensitive season marked by the high development and dominance by encrusting Corallinaceae and opportunistic macroalgal species which can reach high cover.…”
Section: Discussionsupporting
confidence: 81%
“…dredging and filling, propeller scarring) and the release of toxic compounds into coastal waters (e.g. oil spills, industrial discharge) has been discussed by Ben Brahim et al [1,19] and Mabrouk et al [20]. But no studies deal with the effect of natural disturbances such as exposure to wind, wave and tide, on the composition and the abundance of leaf epiphytes in P. oceanica meadows.…”
Section: Introductionmentioning
confidence: 99%
“…; Mabrouk et al . ). Rhizomes constitute a stabile substrate and can therefore host perennial organisms, with consequent low seasonal variation in assemblage structure.…”
Section: Temporal Dynamicsmentioning
confidence: 97%
“…In previous work, C. nodosa beds have been shown in some situations to provide superior foraging returns to fish, which might have been instrumental in this choice. Comparative studies of epifauna on C. nodosa and Posidonia oceanica in the Mediterranean have shown that the epiphyte and epifauna communities associated with C. nodosa can provide equal or even larger quantities of algal and animal food for prey-sized fish [55][56][57][58].…”
Section: Aggressive Predators and Prey Are Negatively Associated At Lmentioning
confidence: 99%